2020
DOI: 10.3390/polym12081709
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Core–Sheath Polymer Nanofibers by Pressurised Gyration

Abstract: The ability to generate core–sheath bicomponent polymer nanofibers in a single-step with scale-up possibilities is demonstrated using pressurised gyration manufacturing. This is the first time that nanofiber containing more than one polymer having a core–sheath configuration has been generated in this way. Water-soluble polymers polyethylene oxide (PEO) and polyvinyl pyrrolidone (PVP) are used as the core and sheath layers, respectively. Core–sheath nanofibers with a diameter in the range of 331 to 998 nm were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Alenezi et al [ 32 ] suggested a new type of approach to loading the metal NPs onto the polymer matrices obtained by pressurized gyration techniques. More recently, Mahalingam et al [ 33 ] created core-sheath configuration through an improved pressurized gyration technique utilizing more than one polymer in a single step on a large-scale technique. However, some of these methods are either expensive, energy-intensive, complicated or require toxic organic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Alenezi et al [ 32 ] suggested a new type of approach to loading the metal NPs onto the polymer matrices obtained by pressurized gyration techniques. More recently, Mahalingam et al [ 33 ] created core-sheath configuration through an improved pressurized gyration technique utilizing more than one polymer in a single step on a large-scale technique. However, some of these methods are either expensive, energy-intensive, complicated or require toxic organic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Whether it is compression or tensile properties, 0.03 m ZnO@BCCS hydrogel shows the best results. Recently, Edirisinghe and co‐workers proposed a method for preparing core–sheath bicomponent polymer nanofibers, [ 37 ] which will provide important inspiration for our future work. In the work of Edirisinghe and co‐workers, water‐soluble polymers polyethylene oxide (PEO) and polyvinyl pyrrolidone (PVP) are used as the core and sheath layers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…copper nanoparticles, whilst the core of the fibres can be a strong polymer which imparts the strength and toughens the mask. This requires upscaling mass production to suit, and work has already been carried out to achieve this [ 16 , 17 ]. However, in parallel, existing respirators and masks need upgrading to properly inhibit the entry of viral particles, and as with Covid-19, these can be smaller than 100nm.…”
Section: Materials and Technologiesmentioning
confidence: 99%